Dealing with teachers’ role stressors and depressive symptomatology: does gender impact on the buffering effect of emotion regulation ability? - Mérida-López, Sergio; Quintana-Orts, Cirenia Luz; Extremera-Pacheco, Natalio; Rey-Peña, Lourdes (My University, 2017)
Certain work-related stressors as role ambiguity and role conflict have been traditionally linked to negative outcomes such as mental health problems. Previous studies have focused on the moderating effect of personal resources in the association between role stressors and work attitudes. Emotion regulation ability (ERA) has showed robust associations with numerous mental health outcomes, with significant gender differences in this relationship.. The purpose of our study was twofold. Firstly, to examine the moderating effect of ERA in the association among role ambiguity/conflict and depressive symptomatology in a teacher sample. Secondly, we aimed to test whether gender would affect the impact of ERA. Participants were 337 Spanish teachers (54.89% were female) from different grade level taught in Malaga. Results showed that ERA moderated the relationship between role ambiguity and depressive symptoms, whereas did not moderate the effect of role conflict. Indeed, gender-specific analysis revealed a three-way interaction of role ambiguity, ERA and gender on depressive symptomatology showing a significant moderation effect only for males. These results suggest underlying processes by which ERA would differently buffer the association between role clarity and depressive symptoms in teachers. Our resultsmay shed some light on showing on testing gender-specific models including work-related factors, emotional abilities, mental health and well-being outcomes in teaching. Finally, these findings might provide guidance in developing further stress management programmes and emotional training considering gender perspectives.
Keywords: Depresión mental; Role stress; Depressive sintomatology; Emotion regulation ability; Teachers